2021
DOI: 10.1155/2021/5537761
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Efficacy of Various Surface Conditioning Methods on the Repair Bond Strength of Composite to Different Fracture Types of Zirconia Ceramics

Abstract: The aim of this study was to investigate the effects of different surface treatment methods on shear bond strength between composite resin and different levels of zirconia ceramic. Laser surface-conditioning procedures have been reported as effective method to increase repair bond strength of composite to zirconia ceramics. Detailed information of effects of Er,Cr:YSGG laser treatment with different pulse rates on the zirconia ceramics is lacking in the literature. 120 disc-shaped specimens were prepared inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Polat et al compared the effectiveness of Er, Cr: YSGG laser with short and long pulse durations to different surface roughening techniques for repairing zirconia ceramics with various surface configurations and found there were no discernible variations among sandblasting and Er, Cr: YSGG laser treatments (Polat, Tokar et al 2021). Tatar and Ural investigated surface treatments for chipping to reduce the problems related to bonding between hybrid materials and composites and found that the most effective method was air abrasion with silica-coated aluminum oxide (Tatar and Ural 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polat et al compared the effectiveness of Er, Cr: YSGG laser with short and long pulse durations to different surface roughening techniques for repairing zirconia ceramics with various surface configurations and found there were no discernible variations among sandblasting and Er, Cr: YSGG laser treatments (Polat, Tokar et al 2021). Tatar and Ural investigated surface treatments for chipping to reduce the problems related to bonding between hybrid materials and composites and found that the most effective method was air abrasion with silica-coated aluminum oxide (Tatar and Ural 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Intraoral repair is a simpler technique to treat veneer ceramic fractures than total replacement or extraoral repair methods (Polat, Tokar et al 2021). Veneering porcelain flaws that expose the restoration's core material create a special challenge for intraoral repair.…”
Section: Introductionmentioning
confidence: 99%
“…141,[172][173][174] Despite recent publications of novel repair techniques, the overall results indicated that solely the mechanical treatment with airborne particle abrasion and bur grinding were efficient to increase the bond strength. 172,175 Additionally, simultaneous use of chemical etching, including 10-methacryloyloxydecyl dihydrogen phosphate (MDP) monomer in a primer and/or adhesive system, has increased bond strength to zirconia systems. 176,177 At present, the polycrystalline ceramic systems, zirconia and zirconia-alumina composites, used in dental restorations are mainly fabricated by uniaxial and isostatic pressing ceramic powders in the form of blocks to be CAD/CAM machined and sintered at high temperatures for long periods to reach high densification; however, some defects can be generated after sintering such as porosities affecting microstructure, optical and mechanical properties of the restorations.…”
Section: Polycrystalline Ceramicsmentioning
confidence: 96%
“…Regarding intraoral repairing procedures in polycrystalline ceramics, especially for zirconia‐based restorations, various surface treatments have been proposed, including airborne particle abrasion with alumina particles or silica‐coated alumina particles, primers, grinding with diamond burs, and laser application (yttrium aluminum garnet (Er:YAG), carbon dioxide (CO 2 ), neodymium‐doped yttrium garnet (ND:YAG), and erbium chromium:yttrium scandium gallium garnet (Er,Cr:YSGG) lasers) 141,172–174 . Despite recent publications of novel repair techniques, the overall results indicated that solely the mechanical treatment with airborne particle abrasion and bur grinding were efficient to increase the bond strength 172,175 . Additionally, simultaneous use of chemical etching, including 10‐methacryloyloxydecyl dihydrogen phosphate (MDP) monomer in a primer and/or adhesive system, has increased bond strength to zirconia systems 176,177 …”
Section: All‐ceramic Systemsmentioning
confidence: 99%
“…Composite resins can be bonded to ceramic substructures, such as zirconia, which are regarded as unetchable with hydrofluoric acid because of their glass-free characteristics. This can be accomplished by utilizing primers that contain adhesive phosphate monomers, which can chemically bond to metal-oxide-containing ceramics while also improving their surface wettability, thereby improving the adhesion ( Blatz et al, 2003 , Meyer-Filho et al, 2004 , Kern, 2009 , Kern, 2015 , Blatz et al, 2016 , Polat et al, 2021 ).…”
Section: Surface Conditioning In Dental Laboratorymentioning
confidence: 99%